An Experimental Study on the Compressibility of Clays Reinforced with Basalt Fiber - Topcuoglu, Yasemin Aslan; Gurocak, Zulfu (My University, 2024)
The use of basalt fiber has become quite common in soil reinforcement works, which emerged as an alternative to traditional soil improvement methods and are carried out using different types of fibers. Basalt fiber, whose raw material is basalt rock, is preferred in soil reinforcement works due to its features such as high strength, economical, environmentally friendly, natural and abundant. In this study, the effects of basalt fiber reinforcement on the compressibility of high plasticity bentonite clay were examined. Bentonite clay was reinforced with 24 mm long basalt fiber at different rates between 0.5% and 5.0%, and standard proctor tests were carried out on these mixtures. With experimental studies, maximum dry density (?dmax) and optimum water content (?opt) values were determined and the effects of basalt fiber reinforcement on these parameters were evaluated. According to the test results, while ?dmax values increased up to 2.5% basalt fiber reinforcement ratio, ?opt values decreased. In samples with basalt fiber ratio greater than 2.5%, ?dmax values decreased and ?opt values increased. The results obtained showed that the basalt fiber ratio at which bentonite can be compressed best is 2.5%, and basalt fiber reinforcement at rates greater than this ratio negatively affects the compressibility.
Keywords: Basalt fiber; Reinforcement; Compressibility; Bentonite clay